Knowledge, attitude and practices of antenatal clients towards prevention of mother to child transmission of hiv in selected districts of Zambia - Ngoma, Yesani; Muyangwa, Nalukui; Nangana, Simataa (Lusaka: University of Zambia , School of Medicine, 2015)
HIV, the virus that AIDS, has become one of the world's most serious health and developmental challenges. The transmission of Hiv infection from mother to the child constitutes a global challenge especially for developing countries. In the absecnce of any intervention, the risk of infection of HIV-exposed children can be as high as 25% for HIV type 1 and 4% for HIV type 2. The purpose of this study to determine knowledge, attitude and practices of antenatal clients towards prevention of mother to child transmission of the HIV to the child.
A study submitted in partial fullfilment of the requirements for the award of a Bachelor of Science Degree in Nursing.
Includes bibliographical references.
Keywords: AIDS (Disease) in infants--Zambia--Prevention.; AIDS (Disease) in pregnancy--Zambia--Prevention.